Khataman Metode Rukū’ Dalam Meningkatkan Semangat Membaca Al-Qur’an (Studi Living Qur’an di Masjid As-Shodiqin) - Rahmalia Fellashofa Regita; Fadhilah Rahmawati (Universitas Nasional, 2025)
This study originates from a phenomenon at As-Shodiqin Mosque, Plosorejo, Ponorogo, where congregants faced limitations in regularly reading the Qur’an before the implementation of the rukū’ method. Previously, Qur’anic reading was conducted only once a week through the recitation of Surah Yasin without a structured system. This research aims to analyze how the rukū’ method can foster a more sustainable culture of Qur’anic reading.Using a phenomenological approach, data was collected through observation, interviews, and documentation. The findings indicate that the rukū’ method helps congregants who had never previously completed a full recitation of the Qur’an. The short, consistent reading segments boost enthusiasm and engagement among participants. Additionally, the implementation of this method strengthens Islamic brotherhood (ukhuwah Islamiyah) through more active interactions and shared religious experiences. Thus, the rukū’ method has proven to be an effective strategy in cultivating a more inclusive and sustainable Qur’anic reading culture at As-Shodiqin Mosque.